Longitudinal Assessment of Examiner Experience and the Accuracy of Sonographic Fetal Weight Estimation at Term. (3rd December 2016) - Faschingbauer, Florian; Heimrich, Jutta; Raabe, Eva; Kehl, Sven; Schneider, Michael; Schmid, Matthias; Beckmann, Matthias W.; Hepp, Tobias; Lübke, Anika; Mayr, Andreas; Schild, Ralf L.
Abstract : Objectives: To evaluate the influence of examiner experience on the accuracy of sonographic weight estimation and to further analyze examiners' individual learning curves. Methods: In this multicenter study, 4613 sonographic weight estimations performed by 18 examiners at the beginning of their ultrasound training were included. To assess the effect of experience on the accuracy of weight estimation, a multivariable mixed regression model analysis was performed, with percentage error and absolute percentage error as outcome variables and the examiner, the examiner's experience (number of examinations), birth weight, gestational age, scan‐to‐delivery interval, and maternal body mass index as fixed effects and the perinatal center as random intercepts. To further analyze the individual learning curves of the examiners, the cumulative summation technique was used. Results: Regression analyses showed a significant influence of the number of examinations on the accuracy of sonographic weight estimation after adjustment for the above‐mentioned parameters ( P < .001). A typical learning curve with improving accuracy was found until approximately 200 examinations. Between 200 and 300 examinations, the diagnostic performance started to deteriorate again, with a continuous decrease until the end of the study period. Cumulative summation charts representing individual learning curves varied greatly between different examiners. Conclusions: These findings indicate the great importance of continuous quality control systems in sonographic weight estimation.